Linguistic proficiency as cultural capital in school environments - Angantýsson, Ásgrímur (Uniwersytet Gdański, 2017)
The main concern of this paper is the extent to which students’ expectations of first language studies reflect the idea that linguistic proficiency produces social and cultural capital (Bourdieu 2008 and earlier work). The participants consisted of 14 focus groups of students in secondary schools in Iceland. Most of the students believe it is desirable to acquire fluency in reading and formal writing. In their view, however, the amount of time devoted to traditional school grammar is actually a detriment to that goal. Furthermore, the students think that success in Icelandic as a school subject depends to some extent on reading habits and language instruction at home. These views support the idea that schools tend to reward their students for knowledge and skills that are not necessarily highlighted in the classroom but which can be viewed as advantageous due to systematic cultural reproduction within families and social networks. Celem niniejszego artykułu jest przedstawienie w jakim zakresie oczekiwania uczniów w stosunku do uczenia się języka pierwszego odzwierciedlają przekonanie, że umiejętności językowe produkują kapitał społeczny i kulturowy (Bourdieu 2008 i wcześniejsze prace). Uczestnikami badania było 14 grup fokusowych skupiających uczniów szkół średnich z Islandii. Większość uczniów uważa, że dobrze jest osiągnąć płynność w czytaniu i posługiwaniu się formalnym językiem pisanym. Ich zdaniem jednak czas poświęcany na uczenie się tradycyjnej gramatyki szkolnej stanowi przeszkodę w osiągnięciu celu. Co więcej, uczniowie są przekonani, że sukces w uczeniu się języka islandzkiego jako przedmiotu szkolnego w pewnym stopniu zależy od zwyczajów czytelniczych i języka używanego w domu. Te przekonania potwierdzają pogląd, że szkoła nagradza uczniów za wiedzę, która niekoniecznie jest wyeksponowana w klasie, ale która może być uważana za korzystną wskutek systematycznej reprodukcji kulturowej w rodzinach i sieciach społecznych.